UNLOCKING THE POTENTIAL ECONOMIC IN UNDEVELOPED REGENCY THROUGH MARITIME INFRASTRUCTURE - Imanuddin Abdul Gani (OISAA, 2018)
The North Kayong Regency is one of the new Regency in West Kalimantan Province that is still lackof infrastructure development such as infrastructure and public amenities. The purpose of thisresearch is to contribute in regional development planning policy through determine appropriate methodin maritime infrastructure for increasing regional economic growth. Our study shows that the bestpractice to improve the development planning process is improve better and appropriate policies thatmight be apply through the new methods on practice oriented, focus on strategies, tools and managethe utilization of planning and resources. By maintain strategies, develop solution that integratesdifferent dimension of regional planning and resources in every conceivable way to solve the problemand to overcome the obstacles.